Agent Orange and Vietnam Veterans: A Review - Young, Alvin Lee; Alexander, Lynda V. (British Journal of Healthcare and Medical Research, 2024)
Issue: Approximately 3 million Allied personnel from the United States, Australia, New Zealand, and the Republic of Korea served in the Republic of Vietnam from March 1965 through March 1973 in what became known as the Vietnam-American War. In March 1978, a widely distributed documentary “Agent Orange: Vietnams Deadly Fog”, generated fear and anger in Vietnam veterans of that War who became aware that the tactical herbicide Agent Orange, a defoliant, had been deployed in combat operations to improve visibility in enemy controlled jungle and infiltration routes, and around base perimeters. One of the herbicidal components of Agent Orange (2,4,5-T herbicide) contained the contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a highly toxic chemical associated with industrial accidents and an alleged teratogen in forestry programs where the herbicide was widely sprayed for brush control and conifer release. Following the release of the documentary, thousands of Allied Vietnam Veterans overwhelmed Veterans Administrations claiming Agent Orange and the associated dioxin were responsible for numerous diseases, birth defects, and long-term health issues. Despite the passage of almost 50 years, science has not been able to answer the question of the health impacts of alleged environmental exposures to either the TCDD or the tactical herbicides on Vietnam veterans. Thus, at the heart of the issues the question remains, were Vietnam veterans ever exposed to Agent Orange and TCDD or was it the Vietnam experience that has impacted the long-term health of the Vietnam veteran? Background: From March 1965 through April 1971, the United States Air Force and the US Army Chemical Corps sprayed approximately 74.2 million liters of tactical herbicides on 1.7 million hectares of the inland forests, savannas, and grasslands of South Vietnam. Contained within the 74.2 million L was 43.3 million L of the tactical herbicide known as Agent Orange that was contaminated with 130 kg of TCDD. Numerous research studies have been conducted in Vietnam, all alleging that the TCDD from Agent Orange was responsible for health issues among the Vietnamese. However, a careful assessment of the sources of TCDD in Vietnam indicated that significant quantities of TCDD were in the waterways and atmosphere due to the pollution from industries and open burning of municipal and industrial wastes, and not from Agent Orange. Human Studies: The deployment of in-country medical support in the War by the Allied Forces was instrumental in saving lives. What was unexpected was that more casualties died from insect-transmitted diseases and other health related issues than from enemy bullets and bombs. The more than 50 health studies of Vietnam veterans by the four Allied nations confirmed that with two exceptions (the Air Force Health Study of veterans from Operation RANCH HAND, and health studies of US Army Chemical Corps personnel) Vietnam veterans were never exposed to Agent Orange or TCDD. What the health studies did confirm was that the “Vietnam Experience” impacted the long-term health of the men and women who served in that war. Policy Considerations: The Congress of the United States, the Department of Veterans Affairs, and the Vietnam veteran simply refuse to accept the reality that little or no exposure to the herbicides or TCDD ever occurred in Vietnam. Instead, the Government continues to expand the lists of diseases and locations through the Agent Orange Act of 1991, and the PACT Act of August 2022. We concur that all Vietnam veterans deserve the best possible health care US and Allied nations can provide, and the recognition they are entitled to for having served in Vietnam. Perhaps the governments would have been fairer with a program of “Vietnam Experience” benefits rather than Agent Orange benefits.